Correlation analysis of lymphocyte surface antigen and THBS1 levels with myocardial injury in sepsis patients: THBS1 levels in sepsis with myocardial injury - Wei, Min; Wang, Wuchao; Wang, Dongxiao; Cheng, Yifei; Liu, Xiaoyu; Xiu, Limei (Journal of Medical Biochemistry, 2026)
Objective To analyze the relationships among the surface antigens of lymphocytes in patients with sepsis, the level of thrombospondin-1 (THBS1), and myocardial injury.Methods 360 sepsis patients who were hospitalized to our hospital between January 2023 and January 2025 were chosen. 170 patients with myocardial injury and 190 patients without myocardial injury were selected from the patient group based on whether or not they had myocardial injury. Serum THBS1 levels, immune function (CD4+, CD8+, and CD4+/CD8+), myocardial injury markers (creatine kinase MB (CK-MB), heart-type fatty acid binding protein (H-FABP), N-terminal pro-B-type natriuretic peptide (NT-proBNP), and cardiac troponin I (cTnI)), and echocardiographic markers (left ventricular ejection fraction (LVEF), early diastolic velocity to atrial contraction velocity ratio (E/A), and cardiac output (CO)) were compared. Correlations between immune function, THBS1 levels, myocardial injury indicators, and echocardiographic markers in individuals with myocardial damage and infection were examined. To predict sepsis with myocardial infarction, the serum THBS1 value was evaluated using the receiver operating characteristic (ROC) curve and the area under the curve (AUC).Results While the myocardial injury group had significantly lower levels of CD8+ T cells in peripheral blood, LVEF, E/A, and CO, the nonmyocardial injury group had significantly higher levels of CD4+, CD4+/CD8+, serum THBS1, CK-MB, H-FABP, NT-proBNP, and cTnI (P
Keywords: Sepsis; T lymphocytes; Immune function; Platelet reaction protein-1; Myocardial injury